2013
DOI: 10.1038/onc.2013.177
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of BMI1 and microRNA-16 collaborate to enhance an anti-apoptotic potential in the side population of refractory mantle cell lymphoma

Abstract: The proto-oncogene BMI1 and its product, Bmi1, is overexpressed in various types of tumors, particularly in aggressive tumors and tumors resistant to conventional chemotherapy. BMI1/Bmi1 is also crucially involved in cancer-initiating cell maintenance, and is recurrently upregulated in mantle cell lymphoma (MCL), especially aggressive variants. Recently, side population (SP) cells were shown to exhibit tumor-initiating characteristics in various types of tumors. In this study, we show that recurrent MCL cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 56 publications
(162 reference statements)
5
61
0
Order By: Relevance
“…[3][4][5][6] Our earlier work also demonstrated miRNA expression in aggressive lymphomas, suggesting that such alterations may be deeply associated with the progression of malignant lymphomas. 9,18,[42][43][44] This makes it tempting to suggest that miR-150 downregulation is a crucial component of advanced CTCL. That remains to be tested, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Our earlier work also demonstrated miRNA expression in aggressive lymphomas, suggesting that such alterations may be deeply associated with the progression of malignant lymphomas. 9,18,[42][43][44] This makes it tempting to suggest that miR-150 downregulation is a crucial component of advanced CTCL. That remains to be tested, however.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that human lymphoma cell lines could be grafted into immunodeficient nonobese diabetic/NOG mice. 18 To examine if transduction of miR-150 might affect tumor formation, we subcutaneously inoculated miR-150-transfected or control cells (2 3 10 5 ; n 5 5 each) into NOG mice, and found that cells expressing miR-150 produced significantly smaller tumors (My-La, MJ, and HUT78), or at least showed a trend toward smaller tumors (HH and ATN-1) (supplemental Figure 2). Furthermore, NOG mice inoculated with GFP-control MyLa cells died within 31 to 37 days, while mice receiving GFP-control HH cells died within 55 to 70 days.…”
Section: Mir-150 Acts As a Tumor Suppressor In T-cell Lymphoma Cellsmentioning
confidence: 99%
“…For example, it has been shown that miR-15/16 inhibits MCL1 oncogene in CLL BMI1 oncogene in mantle call lymphoma. 29,31 Two other recent reports demonstrated that miR-15/16 directly target critical cell cycle regulator Cyclin D1 in bladder cancer and osteosarcoma. 32,33 Another study showed that miR-15/16 expression is downregulated in malignant pleural mesothelioma (MPM).…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 99%
“…miR-17-92 is frequently upregulated in MCL, and because miR-17-92 appears to negatively regulate CDKN1A ⁄ p21, (19) increases in its expression could enhance cell cycle progression. miR-16-1 is expressed normally in MCL, as compared to its expression in normal CD5 + B-cells, (42,43) but Chen et al demonstrate that the 3′UTR of CCND1 is frequently truncated or mutated in MCL, which inhibits the interaction of miR-16-1 with the "seed" sequence of the 3′UTR of CCND1, thereby contributing to continuous upregulation of CyclinD1. (43) In addition, some miRNA have been shown to act as regulators of polycomb-group repressive complex proteins.…”
Section: Microrna Dysregulation Strongly Contributes the Pathogenesismentioning
confidence: 99%